2016
DOI: 10.1038/srep32644
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Screening of Coenzyme Preference Change of Thermophilic 6-Phosphogluconate Dehydrogenase from NADP+ to NAD+

Abstract: Coenzyme engineering that changes NAD(P) selectivity of redox enzymes is an important tool in metabolic engineering, synthetic biology, and biocatalysis. Here we developed a high throughput screening method to identify mutants of 6-phosphogluconate dehydrogenase (6PGDH) from a thermophilic bacterium Moorella thermoacetica with reversed coenzyme selectivity from NADP+ to NAD+. Colonies of a 6PGDH mutant library growing on the agar plates were treated by heat to minimize the background noise, that is, the deacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 51 publications
(59 reference statements)
0
31
0
Order By: Relevance
“…2) indicates that the formation of a new hydrogen bond with NAD + through the replacement of alkaline amino acid by acidic one is favorable to increase the enzyme activity on NAD + , and even reverse the coenzyme preference from NADP + to NAD + . Moreover, our previous research on the directed evolution of Moorella thermoacetica 6PGDH also demonstrated that the introduction of an acidic amino acid, aspartate, in the loop of the Rossmann fold to form a new hydrogen bond with 2′-hydroxyl group of NAD + resulted in a 4,300-fold reversal of coenzyme selectivity from NADP + to NAD +  30. Reports on many other dehydrogenases also confirmed the positive effect of the formation of new hydrogen bond in reversing the coenzyme preference21243031323334.…”
Section: Discussionmentioning
confidence: 94%
“…2) indicates that the formation of a new hydrogen bond with NAD + through the replacement of alkaline amino acid by acidic one is favorable to increase the enzyme activity on NAD + , and even reverse the coenzyme preference from NADP + to NAD + . Moreover, our previous research on the directed evolution of Moorella thermoacetica 6PGDH also demonstrated that the introduction of an acidic amino acid, aspartate, in the loop of the Rossmann fold to form a new hydrogen bond with 2′-hydroxyl group of NAD + resulted in a 4,300-fold reversal of coenzyme selectivity from NADP + to NAD +  30. Reports on many other dehydrogenases also confirmed the positive effect of the formation of new hydrogen bond in reversing the coenzyme preference21243031323334.…”
Section: Discussionmentioning
confidence: 94%
“…Previously, Zhang and his coworkers developed a simple petri dish-based double-layer screening for the identification of mutants of thermophilic NADP-dependent 6-phosphogluconate dehydrogenase with enhanced catalytic efficiencies on NAD ϩ . In this screening, the reduced NADH can react with the redox dye TNBT, generating black TNBT formazan (27). This screening method cannot be applicable to ultrathermophilic enzymes due to low melting temperatures of agar or agarose.…”
Section: Resultsmentioning
confidence: 99%
“…The E. coli TOP10 is a good strain for mutant library construction because of the high transformation efficiencies (e.g., 10 8 to 10 9 CFU/g plasmid DNA) ( Table 1). However, its ability for recombinant protein expression is much lower than that for E. coli BL21(DE3) based on the pET expression system, which suffers from low transformation efficiency (e.g., 10 6 CFU/g plasmid DNA) (27). To fulfill high transformation efficiency for directed evolution in E. coli TOP10 and high protein expression in E. coli BL21(DE3), an inducible tac promoter was inserted into pET28a-ppgk ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations